Regulating the N-oxidation selectivity of P450BM3 monooxygenases for N-heterocycles through computer-assisted structure-guided design - Liu Yang; Zhongji Pu; Jianping Wu; Xiaofeng Liu; Zhe Wang; Haoran Yu; Liuwei Wang; Yan Meng; Gang Xu; Lirong Yang; Wenlong Zheng (Nature Communications)
Abstract N-oxidation of N-heterocycles is essential in the synthesis of natural products but challenging due to low efficacy and poor regioselectivity. In this study, the N-oxidation selective potential of P450BM3 from Bacillus megaterium for N-heterocyclic compounds is investigated. Here, twelve amino acids located in the active center, including A74, L75, V78, A82, F87, I263, A264, A328, P329, A330, I401, and L437, are investigated by site-saturation mutation. As a result, F87, A264, L75, V78, A328, I401, and L437 are identified as hotspot residues. Subsequently, the combinatorial active-site saturation test/iterative saturation mutagenesis strategy is performed. Using quinoline as a model substrate, the mutant F87G/A264G/A328L exhibits N-oxidation selectivity of up to 99.0%, with a conversion rate of 99.3%. Molecular dynamics simulations uncover a “push-pull” molecular mechanism elucidating the pivotal role of steric factors in determining substrate recognition and N-oxidation selectivity. This study provides an efficient N-oxide synthesis method and insights into P450BM3’s molecular mechanisms.